EFEKTIVITAS PESTISIDANABATI TERHADAP SERANGAN HAMA PADA BAYAM CABUT (Amaranthus hibrydus L) DENGAN BEBERAPA DOSIS PUPUK N - FitriyanSwasono; Mohamad Ihsan, Tri Pamujiasih (PROSIDING, 2022)
Research objectives were to evaluated the effect of bio-pesticides from neem seed extract and various types of nitrogen fertilizer doses. This research was conducted on May 9, 2019 until June 2, 2019 in Gumpang Village, Kartasura Sub-District, Sukoharjo Regency, with a place height of ± 110mpl.Experimental design used was factorial method with a basic pattern of completely randomized design, consisting of two factors with four reaplications. The first factor was the use of neem extract (F) consisting of two types (F0 = without extract and, F1 = 20cc extract mixed with 80 ml of water). The second factor, the various types of Nitrogen fertilizer doses consisting of four types (N0 = 0 g / plant, N1 = 0,45 g / plant, N2 = 0,9 g / plant, N3 = 1,35 g / plant). Results showed that the application of neem seed extract and the treatment of various types of Nitrogen fertilizer doses and the interaction between these treatments had a highly significant effect at all parameters of observation. The application of neem seed extract can increase plant height, the number of leaves of each plant, fresh weight of plant, plant volume and reduce the percentage of pest attack on spinach plants. Giving a dose of Nitrogen fertilizer can increase plant height, plant number of leaves, plant volume of fresh plant weight, but increase the percentage of pest attacks. At the F1N3 combination treatment (the application of neem seed extract and dose of 1,35g Nitrogen fertilizer / plant) showed the highest average yield in all parameters. But the pest attacks precentage pull out the best results 9,98 obtained in F1N2 combination (the application of neem seed extract and 0,9g Nitrogen / plant fertilizer dose). Keywords : bio pesticide, neem, nitrogen, effectivity, spinach